Clicker를 활용한 한국어 교실 상호 작용 증진 방안 연구 = A study on method for promoting interaction in L2 classroom using clickers - Ryoo, Agnes Hye Jin 류혜진 (2020)
This study aims to find the method to promote interaction in L2 classrooms. Active interaction between learner-to-learner and learner-to-teacher in L2 classroom plays an important role in language acquisition. In light of this, L2 classroom would benefit with the help of learning tools such as Clickers which helps learners to express their level of understanding during the process of learning itself. This is because the anonymity of Clickers allows learners to express their needs without the social risks associated with speaking up in the class. It allows for an evaluative feedback loop where both learners and teachers understand the level of progress of the learners, better enabling classrooms to adapt to the learners’ needs. Eventually this tool promotes participation from learners, This is in turn, believed to be effective in fostering classroom interaction, allowing learning to take place in a more comfortable yet vibrant way. This study is finalized by presenting the result of an experiment conducted to verify the effectiveness of this approach when teaching pragmatic aspect of the Korean expressions with similar semantic functions. As a result of the research, the learning achievement of learners in the experimental group was found higher than the learners’ in a control group. Analyzing the data collected from a questionnaire given to the learners, the study presented data suggesting that this approach increased the scope of interactivity in the classroom, thus enhancing more active participation among learners. This active participation in turn led to a marked improvement in their communicative abilities.